The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.2500/ajra.2012.26.3738
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-exacerbated Respiratory Disease in China: A Cohort Investigation and Literature Review

Abstract: Background: Although the prevalence of aspirin-exacerbated respiratory disease (AERD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
3
27
0
1
Order By: Relevance
“…In a recent random sample survey study with over 52,000 adults aged 18 to 75 years in 12 European countries, the prevalence of self-reported current asthma (5.1-16.8%) was found to be strongly associated with CRS appropriate symptoms (adjusted OR, 3.47; 95% CI, 3.20 to 3.76) in all ages, in both men and women, irrespective of smoking behavior. 293 The reported incidence of asthma varies from 2% to 38% in patients with CRS, [294][295][296][297][298][299] 2% to 66% in CRSwNP, 289, and 68% to 91% in refractory CRSwNP. 290,299 Among these reports, the prevalence of asthma in patients with CRSsNP or CRSwNP appears to be lower in Asians than whites.…”
Section: Viib Crssnp: Comorbid Asthmamentioning
confidence: 99%
“…In a recent random sample survey study with over 52,000 adults aged 18 to 75 years in 12 European countries, the prevalence of self-reported current asthma (5.1-16.8%) was found to be strongly associated with CRS appropriate symptoms (adjusted OR, 3.47; 95% CI, 3.20 to 3.76) in all ages, in both men and women, irrespective of smoking behavior. 293 The reported incidence of asthma varies from 2% to 38% in patients with CRS, [294][295][296][297][298][299] 2% to 66% in CRSwNP, 289, and 68% to 91% in refractory CRSwNP. 290,299 Among these reports, the prevalence of asthma in patients with CRSsNP or CRSwNP appears to be lower in Asians than whites.…”
Section: Viib Crssnp: Comorbid Asthmamentioning
confidence: 99%
“…Specifically, in some regions of Asia, it has recently been shown that some CRSwNP cases (nearly 50%) are more likely to be associated with a noneosinophilic or neutrophilic infiltrate and Th1/17 cytokine skewing [41][42][43][44]. In correlation with reduced eosinophilic inflammation, we also observed a very low rate of concomitant asthma and aspirin-exacerbated respiratory disease in Chinese CRSwNP patients [45,46]. It is also interesting to note that over a 12-year period (from 1999 to 2011), a shift from predominantly neutrophilic to eosinophilic inflammation was recently reported in Asian (Thai) patients with CRSwNPs in association with an increase in the intramucosal presence of Staphylococcus aureus [47].…”
Section: Endotypes Of Chronic Rhinosinusitis: Eosinophilic Versus Nonmentioning
confidence: 48%
“…These observations would in turn suggest that Asian patients, given their relative paucity of tissue eosinophils, might be less likely to have AERD. This is supported by one small study from China that found the prevalence of AERD to be 0.57% among patients evaluated with CRSwNP 48 , which is must lower than the 9–10% estimated in a meta-analysis of patients predominantly of European descent 6 . Second generation Asians with CRSwNP in the US also had less atopy and less comorbidity with asthma than non Asian Americans.…”
Section: Disease Pathophysiologymentioning
confidence: 74%
“…mast cells, eosinophils, and basophils), it is not surprising that there are elevations in levels of traditional type-2 inflammatory mediators in AERD and also in CRSwNP nasal polyps when compared to healthy sinonasal tissue (e.g. IL-5, IL-4, IL-13, Eotaxin-1 Eotaxin-2) 43, 4448, 45, 75, 76 .…”
Section: Disease Pathophysiologymentioning
confidence: 99%